2000
DOI: 10.1097/00004872-200018020-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant treatments on nitrate tolerance development in normotensive and hypertensive rats

Abstract: aObjectives To investigate the effect of chronic antioxidant treatments on the development of nitrate tolerance in spontaneously hypertensive (SHR) and normotensive Wistar±Kyoto (WKY) rats by evaluating (i) coronary vascular reactivity, (ii) lipid peroxidation (malondialdehyde), and (iii) peroxynitrite formation (3-nitrotyrosine).Methods Tolerance was induced in 16-week-old male SHR and WKY, by 4 days of continuous treatment with nitroglycerin patches. Two groups were orally pre-treated (2-weeks) with antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Increased levels of oxidative stress have been described in experimental models of hypertension (2,6,20) and hypertensive patients (22,35). Treatment with a variety of antioxidants has been shown to decrease arterial blood pressure in several experimental and genetic models of hypertension (4,7,30,40,48). Several groups also demonstrated the association between elevated levels of intrarenal ROS and renal damage (44), and the deleterious effects that deficiencies in catalase (21,24) or superoxide dismutase (26,37) have on renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of oxidative stress have been described in experimental models of hypertension (2,6,20) and hypertensive patients (22,35). Treatment with a variety of antioxidants has been shown to decrease arterial blood pressure in several experimental and genetic models of hypertension (4,7,30,40,48). Several groups also demonstrated the association between elevated levels of intrarenal ROS and renal damage (44), and the deleterious effects that deficiencies in catalase (21,24) or superoxide dismutase (26,37) have on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with a variety of antioxidants reduces blood pressure in several genetic and experimental models of hypertension (4,7,30,40,48). One of the most important biological mechanisms for the production of ROS results from the generation of superoxide (O 2 ·Ϫ ) from O 2 by the enzyme NADPH oxidase (14).…”
mentioning
confidence: 99%
“…These values are more than 1000 times higher than those measured by GC-tandem MS in the present study in healthy humans. The HPLC-UV method applied in that study has been originally developed to measure 3-nitrotyrosine in coronary sinus effluent in rats [19]. This HPLC-UV method has not been validated for this matrix or urine and plasma from humans [16].…”
Section: Basal Levels Of 3-nitrotyrosine In Human Urinementioning
confidence: 99%
“…Pannala et al (1998) reported that hydroxycinnamates antioxidants decreased peroxynitrite-mediated nitration of tyrosine in vitro. Cabassi et al (2000) showed that the antioxidants N-acetyl-L-cysteine and melatonin reversed the formation of 3-nitrotyrosine in rat heart. The addition of 7-nitroindazole, a nitric oxide synthase inhibitor, suppressed the formation of 3-nitrotyrosine to below the detection limits in the early phase following reperfusion of mouse brain (Hirabayashi et al, 1999).…”
Section: -Nitrotyrosinementioning
confidence: 99%